Publikasiegereed? Oor die aanbiedingswyse, keuringsprosedure en teksversorging van navorsingsartikels - Venter, M. (Koers, 2001)
Ready to publish? On the presentation, refereeing process and text editing of scholarly articles This article is an attempt to present authors planning to write a scholarly article with practical guidelines before submitting the article to a specific journal. The following aspects are also focused on: typical points of criticism usually raised in referees’ reports, and the necessity for clarity of expression and lucid scholarly style. Specific examples of how to enhance the technical and language finish of an article are also included. This article is the outcome of many years of practical work within the Bureau for Scholarly Journals; hence the publication of it in Koers, one of the journals processed by the Bureau.